Harmonisasi Peraturan Perpajakan dalam Pandangan UMKM - Mariana, Hana; Ervina, Deasy (JFAS : Journal of Finance and Accounting Studies, 2024)
The purpose of this study is to analyze more deeply regarding the HPP Law in the eyes of MSME actors in the Jombang region. This type of research is qualitative with primary data sources. The object of this study was at KPP Pratama Jombang and had 30 informants. Data collection techniques using source triangulation consisting of observation, documentation and interviews. The results of the research show that the HPP Law does not reflect justice. Nonetheless, the contribution and compliance of WP OP UMKM according to Jombang KPP Pratama data increased when the HPP Law was enacted. This is due to changes in the turnover limit of the HPP Law, where the tax burden will be less when compared to the previous law, thus having good implications for compliance with WP OP UMKM at KPP Pratama Jombang.